Estudo sobre mediação e desenvolvimento humano na teoria de Vigotski: reflexões sobre a criança em situação de adoecimento - Pimenta, Stéfany Bruna de Brito (2017)
This thesis aims to understand the conception of human development in Vygotskian theory and then, from such foundations, make considerations about the development of the child in sickness situation. While a theoretical research, the work was development through the study of some important works of Vygotsky that discuss about the human development and, specifically, the development of the child, which is "History of the development of the superior psychic functions"; "Problems of Child Psychology"; "Fundamentals of Defectology" and "Thought and Language". An exploratory bibliographical survey was also carried out with the objective of identifying other materials that contribute to the discussion of the subject in question. In the study of Vigotskian theory it was possible to identify fundamental concepts that allow a historical-cultural understanding of the development of the child and, consequently, base their problematization in diverse situations. It is identified that the conception of human development of the Vygotskian theory, based on dialectical historical materialism, breaks with biological dichotomies, determinisms and reductions, contributing to the construction of a dialectical approach in the field of health. Thus, from the understanding of some concepts that allow the understanding of the development of the child, such as "mediation", "experience", "social development situation", it became feasible to elaborate a theoretical essay that reflects aspects of the child’s development in the situation of physical illness. It is hoped that this research will contribute to the theoretical foundation of professionals and reseachers with interfaces between psychology and the health area, especially child’s health.